A Previously Undescribed Presentation of Mixed Adenoneuroendocrine Carcinoma - De Luca-Johnson, Javier (Case Rep Pathol, 2016)
We report a case of mixed adenoneuroendocrine carcinoma (MANEC) of stomach with tubular adenoma and well-differentiated neuroendocrine tumor (WD-NET) in the primary tumor in the stomach giving rise to biphenotypic regional nodal metastases. A 35-year-old woman with abdominal pain was found to have a 1.8-cm gastric lesion, diagnosed as WD-NET (intermediate grade) on the biopsy. The resection specimen contained residual WD-NET; there was also a gastric adenoma adjacent to the NET and nodal metastasis with both adeno- and neuroendocrine components. The tumor was classified as MANEC. Of note, the entire gastric tissue was submitted and multiple deeper levels of the adenomatous lesion were examined; no adenocarcinoma was present in the primary lesion. While association of gastric adenoma with neuroendocrine neoplasm is rare, presence of biphenotypic metastasis originating from such a lesion is highly unusual and to the best of our knowledge has not been reported.